Biological characterization and genomic analysis of the newly discovered mycobacteriophage WST1 - Xingyan Tan; Xiaorui Zhang; Zhiqun He; Zhiping Luo; Ni An; Kerui Ye; Donghui Ke; Yuqing Li; Jumei Zeng (BMC Microbiology)
Abstract The rising prevalence of multidrug-resistant mycobacteria necessitates novel therapeutic strategies. Phages targeting clinically relevant mycobacteria remain scarce, lytic phages represent promising alternatives. In this study, we isolated mycobacterium phage WST1 from wastewater, exhibiting strict lytic specificity for Mycobacterium smegmatis. Genomic analysis revealed a 38,120 bp dsDNA genome (64.60% GC) with 59 ORFs, including tyrosine integrase, hicA/B toxin-antitoxin, but no virulence or resistance genes. WST1 demonstrated broad thermal stability (4–60℃) and pH (4–9) stability, but is UV-sensitive. Phylogenetically, WST1 formed a distinct clade with mycobacterium phage IdentityCrisis, the average nucleotide identity is 83.9%, WST1 possesses a terminase which shows 100% amino acid identity to IdentityCrisis, while its endolysin shows over 90% identity to other distant phages, showcasing the modular evolution of WST1.We discovered a new, safe phage candidate useful for both phage diversity studying and genetic engineering, thereby expanding the resources for mycobacteriophage therapeutic development.